Hepatoprotective role of Legalon 70 against hydrogen peroxide in chickens: Hepatoprotective Role of Legalon70 against H2O2 in Chickens - Alkatib, Samera M.; Ismail, May K.; AlMoula, Alaa H.; Alkennany, Intesar R. (International Journal of Health Sciences, 2019)
Objectives: This study aimed at evaluating the effect of Legalon 70, a standard hepatic drug of silymarin, in reducing the toxic effects of hydrogen peroxide (H2O2) in broiler chickens. Methods: Twenty Ross broiler chickens of 30-day old were divided into four groups, Group 1 control, received drinking tap water, Group 2 treated with 0.5% H2O2 in drinking water, Group 3 treated with 0.5% H2O2 and 3 mg/Kg Legalon 70 daily, and Group 4 treated with a single oral dose of 3 mg/Kg Legalon 70 daily. After 4 weeks of the treatment, chickens were killed and the serum collected for the measuring of liver functions parameters, and the liver tissues used for processing the histological examination. Results: The results indicated that H2O2 treatment significantly elevated serum aspartate aminotransferase and alanine aminotransferase, and bilirubin level (direct and total) and decreased level of serum albumin comparing with control group. Treatment with Legalon 70 significantly reversed the H2O2-induced alteration and has positive effects on the liver functions parameters. Results of histopathology of H2O2-treated group showed severe vascular congestion, alveolar damage, and inflammatory cell infiltration, silymarin treatment blocked these changes and reduced the toxic effects of H2O2 toward liver cells. Conclusion: We concluded that silymarin induces the liver function recovery and considered in the treatment of liver injury. Silymarin, a major component of milk thistle, has been used as a hepatoprotector.